Old Testament law for Christians : original context and enduring application - Gane, Roy, 1955- (Grand Rapids,MI Baker Academic, 2017)
"Christians have often neglected the wisdom of the Old Testament laws because they have been viewed as irrelevant, obscure, disturbing, or only useful as "moral laws". In Old Testament Law for Christians, Roy E. Gane, a leading evangelical expert in biblical law, helps readers understand the Old Testament law, how it functioned in the Old Testament, and how it is and is not instructive for contemporary Christians. This is accomplished by providing a detailed explanation of the law's purpose, as well as looking at the literary and historical background of ancient Israel. Gane proceeds to analyze extensively both the application and value of the Old Testament law. The aim of this work is to aid Christians, especially those who teach others, in understanding how Old Testament laws reveal wise and enduring values and principles, even when certain laws might not directly apply to us today." -- !c From publisher's description.
"The Old Testament law is foundational for our understanding of the Bible, but for many it remains some of the Old Testament's most foreign and exotic material. This book by a leading evangelical expert in biblical law helps readers understand Old Testament law, how it functioned in the Old Testament, and how it is (and is not) instructive for contemporary Christians. The author explicates the often confusing legal system of ancient Israel, differentiates between time-bound cultural aspects of Israelite law and universally applicable aspects of the divine value system, and shows the ethical relevance of Old Testament law for Christians today." -- !c From amazon.com.
Getting into Old Testament law -- Is Old Testament law relevant for new-covenant Christians? -- What is Old Testament law? -- The purpose of Old Testament law -- Literature and background of Old Testament law -- Navigating Old Testament laws and related literature -- How does the Old Testament law genre inculcate values? -- Historical contexts illuminating Old Testament laws -- Applying applying Old Testament laws -- Introduction to applying Old Testament laws to Christian life -- Approaches to applying Old Testament law -- Progressive moral wisdom -- Case study of progressive moral wisdom: lost and profound in Exodus 23:4 -- Values in Old Testament law -- Ten Commandments and related laws, part one -- Ten Commandments and related laws, part two -- Social justice in Old Testament law -- Old Testament law and theodicy -- Questions about keeping Old Testament laws today -- Values reflected in ritual laws -- Conclusion : the value of obedience to God.
Includes bibliographical references and indexes.
Keywords: Law (Theology); Christianity and law